Muslims in the United States - Bā-Yūnus, Ilyās (Greenwood Press, 2006)
Introduction -- Islam as a creed and a world religion -- Estimating the Muslim American population -- The Muslim activist : organizing Islam in America -- Minarets on the skyline : the culture of the Muslim community -- The Muslim woman in America -- Guilty until proven innocent : the aftermath of 9/11 -- Major internal concerns